IPTEKS EVALUASI EFEKTIVITAS PROSEDUR PENCAIRAN DANA HIBAH PADA BADAN PENGELOLA KEUANGAN DAN ASET DAERAH PROVINSI SULAWESI UTARA - Manoppo, Mentari P.; Pioh, Felly T.C.; Rungkat, Via E.; Sondakh, Jullie J. (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
Grants are types of assistance that are not returned. Grants can be given to other parties and also can be received from other parties. The procedure for disbursing grants in government institutions must run effectively and in accordance with applicable regulations. The North Sulawesi BPKAD becomes the object under study. The method that applied in this study is evaluating the effectiveness of the grant disbursement procedure in accordance with Peraturan Menteri Dalam Negeri Nomor 32 Tahun 2011. The technique used is to make a comparison between the procedures for disturbing grants made by The North Sulawesi BPKAD with the procedure of grant funds according to Peraturan Menteri Dalam Negeri Nomor 32 Tahun 2011. The result of this study indicate that The North Sulawesi BPKAD has carried out procedures for disbursing grants in accordance with Peraturan Menteri Dalam Negeri Nomor 32 Tahun 2011.Keywords: Evaluating, Effectiveness, Grant Disbursement Procedure